PEMANFAATAN SITUS BATU PERSIDANGAN SEBAGAI SUMBER PEMBELAJARAN SEJARAH - Friska Panjaitan; Corry Corry; Ulung Napitu (Prodi Pendidikan Guru Sekolah Dasar (PGSD) FKIP Universitas Pattimura, 2023)
Historic sites should be optimally utilized as an alternative source of learning. The trial stone site in Samosir is a source of learning history, especially learning pre-script history. The method used in this study is a qualitative method which will provide an overview of the variables studied. This method was determined because the data collected is qualitative data taken from the results of interviews with various sources and students' responses to the learning process. The procedures carried out are identifying site objects, identifying the values ​​contained, making lesson plans, evaluating student responses, and concluding research results. The learning outcomes by utilizing historical sites such as stone trial sites not only increase students' knowledge of pre-literate material, but can also develop good character in students. Through exploration of the trial stone site, students will get a lot of teaching that is not only cognitive, but also affective and psychomotor will be actively involved when the learning process is carried out.